Molecular rearrangements in organic synthesis - Rojas, Christian Miguel (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Designed for practitioners of organic synthesis, this book helps chemists understand and take advantage of rearrangement reactions to enhance the synthesis of useful chemical compounds. -Provides ready access to the genesis, mechanisms, and synthetic utility of rearrangement reactions -Emphasizes strategic synthetic planning and implementation -Covers 20 different rearrangement reactions -Includes applications for synthesizing compounds useful as natural products, medicinal compounds, functional materials, and physical organic chemistry.
1,2-migrations. Pinacol and semi-pinacol rearrangements in total synthesis -- Baeyer-Villiger (BV) oxidation/rearrangement in organic synthesis -- The Wolff rearrangement : tactics, strategies and recent applications in organic synthesis -- Alkyl and acyl azide rearrangements -- Beckmann rearrangements and fragmentations in organic synthesis -- Brook rearrangement. 1,2-migrations via three-membered rings. The quasi-favorskii rearrangement -- The Ramberg-Backlund reaction -- Applications of di-pi-methane and related rearrangement reactions in chemical synthesis. 1,3-transpositions. Payne rearrangement -- Vinylcyclopropane-cyclopentene rearrangement -- Ferrier carbocyclization reaction. [3,3]- and [2,3]-sigmatropic rearrangements. The Claisen rearrangement -- [3,3]-sigmatropic rearrangements with heteroatom-heteroatom bonds -- [2,3]-rearrangements of ammonium zwitterions -- Oxonium ylide rearrangements in synthesis -- The [2,3]-Wittig rearrangement -- The Mislow-Evans rearrangement. Ipso rearrangements. Smiles rearrangements -- Pummerer-type reactions as powerful tools in organic synthesis.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Rearrangements (Chemistry); Organic compounds -- Synthesis; SCIENCE -- Chemistry -- Organic; Organic compounds -- Synthesis; Rearrangements (Chemistry); Electronic books